The Academy, the Otherworld and Between - Rountree, Kathryn (The pomegranate, 2015)
The paper discusses twenty-five years of research, beginning with feminist witches in New Zealand, moving to the small but diverse Pagan community of Malta, then to European Pagan communities more broadly, and recently to larger themes pertinent to Paganisms globally, such as nationalism, trans-nationalism, cosmopolitanism, and local/global influences and processes. My career and this paper are preoccupied with researcher and Pagan identities and positioning, and with the socio-cultural contexts in which they are crafted, including the academic one. An anthropologist is always and inevitably, to some degree, a liminal being, whose position as a perpetual 'in-betweener' has long been problematized within the discipline. For those who research witches and Pagans, this liminality is amplified because our research participants, too, are liminal in the societies they inhabit, and because seeking liminality - or going 'between the worlds' - is fundamental to Pagan rituals and everyday life. In this narrative I show that while an anthropologist's positioning is inherently problematic, liminality can be comfortable and explicable by employing the metaphor of the hag who, though liminal, can fully occupy multiple worlds.